Define the Market for Charitable Trust which would be willing to fund Working for Youth Project - Malla, Biraj (2012)
The experience of unemployment can be particularly damaging for young people, as evidence shows that those who experience prolonged worklessness when they are young are likely to suffer lifelong effects on both earnings and employment prospects(Paul Bivand, 2012). For this reason tackling youth unemployment needs to be a policy imperative. Nick Hurd Minister for Civil Society said: “We must ensure that we harness the energy and innovation of our young people and ensure that they get sustainable jobs with career development opportunities. The government recognizes that Voluntary, Community and Social Enterprise organizations have unique skills and experience in addressing this important issue(Cabinet Office, 2012).